Diet patterns are associated with demographic factors and nutritional status in South Indian children. Issue 1 (2nd July 2013) - Kehoe, Sarah H.; Krishnaveni, Ghattu V.; Veena, Sargoor R.; Guntupalli, Aravinda M.; Margetts, Barrie M.; Fall, Caroline H.D.; Robinson, Sian M.
Abstract The burden of non‐communicable chronic disease (NCD) in India is increasing. Diet and body composition 'track' from childhood into adult life and contribute to the development of risk factors for NCD. Little is known about the diet patterns of Indian children. We aimed to identify diet patterns and study associations with body composition and socio‐demographic factors in the Mysore Parthenon Study cohort. We collected anthropometric and demographic data from children aged 9.5 years (n = 538). We also administered a food frequency questionnaire and measured fasting blood concentrations of folate and vitamin B12. Using principal component analysis, we identified two diet patterns. The 'snack and fruit' pattern was characterised by frequent intakes of snacks, fruit, sweetened drinks, rice and meat dishes and leavened breads. The 'lacto‐vegetarian' pattern was characterised by frequent intakes of finger millet, vegetarian rice dishes, yoghurt, vegetable dishes and infrequent meat consumption. Adherence to the 'snack and fruit' pattern was associated with season, being Muslim and urban dwelling. Adherence to the lacto‐vegetarian pattern was associated with being Hindu, rural dwelling and a lower maternal body mass index. The 'snack and fruit' pattern was negatively associated with the child's adiposity. The lacto‐vegetarian pattern was positively associated with blood folate concentration and negatively with vitamin B12 concentration. This study provides new information on correlates of diet patterns in Indian children and how diet relates to nutritional status. Follow‐up of these children will be important to determine the role of these differences in diet in the development of risk factors for NCD including body composition.